2008
DOI: 10.1210/en.2008-0269
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor 30 Localizes to the Endoplasmic Reticulum and Is Not Activated by Estradiol

Abstract: The classical estrogen receptor (ER) mediates genomic as well as rapid nongenomic estradiol responses. In case of genomic responses, the ER acts as a ligand-dependent transcription factor that regulates gene expression in estrogen target tissues. In contrast, nongenomic effects are initiated at the plasma membrane and lead to rapid activation of cytoplasmic signal transduction pathways. Recently, an orphan G protein-coupled receptor, GPR30, has been claimed to bind to and to signal in response to estradiol. GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
169
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(194 citation statements)
references
References 33 publications
17
169
2
6
Order By: Relevance
“…9) may contribute to nongenomic signaling of E 2 important for breast cancer pathophysiology. Furthermore, the S1P receptors may be the G protein-coupled receptors that mediate rapid nongenomic responses to E 2 rather than GPR30, which has been shown to be present in endoplasmic reticulum, not the plasma membrane (17,53). Our work, taken together with the criss-cross model for E 2 signaling proposed by Sukocheva et al (19), suggests that E 2 stimulates SphK1, increasing production of S1P in the vicinity of the ABC transporters, ABCC1 and ABCG2, at the plasma membrane, which facilitate its export (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9) may contribute to nongenomic signaling of E 2 important for breast cancer pathophysiology. Furthermore, the S1P receptors may be the G protein-coupled receptors that mediate rapid nongenomic responses to E 2 rather than GPR30, which has been shown to be present in endoplasmic reticulum, not the plasma membrane (17,53). Our work, taken together with the criss-cross model for E 2 signaling proposed by Sukocheva et al (19), suggests that E 2 stimulates SphK1, increasing production of S1P in the vicinity of the ABC transporters, ABCC1 and ABCG2, at the plasma membrane, which facilitate its export (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that GPR30 is a membrane-associated ER added a novel dimension to the complexity of estrogen signaling. Controversy exists, however, regarding whether GPR30 is truly an ER (Levin 2009, Langer et al 2010, with several studies showing that GPR30 directly binds E 2 (Revankar et al 2005, Thomas et al 2005, Thomas & Dong 2006 and another study showing that it does not (Otto et al 2008). It also remains unclear whether GPR30 localizes to the plasma membrane (Funakoshi et al 2006, Filardo et al 2007 or to the endoplasmic reticulum (Revankar et al 2005, Otto et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists, however, regarding whether GPR30 is truly an ER (Levin 2009, Langer et al 2010, with several studies showing that GPR30 directly binds E 2 (Revankar et al 2005, Thomas et al 2005, Thomas & Dong 2006 and another study showing that it does not (Otto et al 2008). It also remains unclear whether GPR30 localizes to the plasma membrane (Funakoshi et al 2006, Filardo et al 2007 or to the endoplasmic reticulum (Revankar et al 2005, Otto et al 2008. GPR30 clearly mediates components of estrogen signaling, as evidenced by multiple studies that confer estrogen responsiveness by inducing GPR30 expression or repress estrogen signaling via GPR30 knockdown or inhibition (reviewed in Prossnitz & Maggiolini (2009) and Maggiolini & Picard (2010)).…”
Section: Discussionmentioning
confidence: 99%
“…Our initial task was to verify a parameter for GPER/GPR30 activity. Despite evidence that GPER/GPR30 was a G␣ s -associated GPCR (1), it has been shown that 17␤-estradiol failed to stimulate cAMP production in cells endogenously expressing GPER/GPR30 or heterologously overexpressing the receptor (37,38). More recently, it was shown that neither 17␤-estradiol nor GPER/GPR30 agonist G-1 stimulated cAMP production in cells overexpressing GPER/GPR30 and that GPER/GPR30 constitutively inhibits adenylyl cyclase-mediated cAMP production by interacting with the MAGUKs and AKAP5 (15).…”
Section: G-1 Inhibits Camentioning
confidence: 99%